Risk factors for flow-related aneurysm rupture associated with posterior circulation arteriovenous malformation: a multicenter retrospective study - Yifei, Wang; Guangxi, Li; Chenyuan, Li; Shu, Chen; Leocardia, Chekera Ropafadzo; Hanxiao, Chang; Han, Luo; Wenyan, Li; Zheng, Li; Chao, Lin; Xiupeng, Xu; Zhi, Chen; et al. (Frontiers in Neurology, 2025)
BackgroundFlow-related aneurysms (FAs) are more common and have an increased risk of rupture in posterior circulation arteriovenous malformations (pAVMs). However, the risk factors for FA rupture in pAVMs are understudied and warrant further investigation.ObjectiveThis study aimed to investigate the risk factors for FA rupture associated with pAVMs using a multi-centric database from 1 January 2020 to 31 December 2024.MethodsPatients diagnosed with AVMs were selected from databases. Patients with ruptured FAs and those with unruptured FAs were compared. Independent Student’s t-test, Mann–Whitney U-test, Fisher’s exact test, and multivariable binary logistic regression were used for analysis.ResultsAmong 284 patients, 37 patients with 22 ruptured FAs and 28 with unruptured FAs met the inclusion criteria. The results indicated that ruptured FAs were associated with smaller pAVMs (2.41 ± 1.02 cm vs. 3.93 ± 2.68 cm, p = 0.001) and Spetzler–Martin grades I to II (p = 0.013). Patients with ruptured FAs had greater aneurysm size [median size, 4.55 mm (IQR, 3.20–7.55 mm) vs. 3.00 mm (IQR, 2.40–5.00 mm); p = 0.009], larger size ratio [median, 2.72 (IQR, 1.95–4.12) vs. 2.23 (1.10–2.87); p = 0.021], and larger relative size ratio [median, 0.24 (IQR, 0.137–0.358) vs. 0.096 (IQR, 0.063–0.129); p < 0.001] than those with unruptured FAs. The multivariable binary logistic regression analysis indicated that only the AVM size [OR, 0.92 (95% CI, 0.84–0.99); p = 0.039] and the size ratio [OR, 1.66 (95% CI, 1.07–2.59); p = 0.024] remained associated with the risk of rupture.ConclusionThe size of pAVMs and size ratio of FAs to average diameter of the parent vessel are independent risk factors for FA rupture associated with pAVMs.